2013 European guideline for the management of balanoposthitis. (August 2014) - Edwards, SK; Bunker, CB; Ziller, Fabian; van der Meijden, Willem I
Balanoposthitis can be caused by a disparate range of conditions affecting the penile skin. This guideline concentrates on a selected group of conditions and offers recommendations on the diagnostic tests and treatment regimens needed for the effective management of balanoposthitis.